2007
DOI: 10.1093/cercor/bhm223
|View full text |Cite
|
Sign up to set email alerts
|

Selective Activation of Medial Prefrontal-to-Accumbens Projection Neurons by Amygdala Stimulation and Pavlovian Conditioned Stimuli

Abstract: Medial prefrontal cortex (mPFC) neurons respond to Pavlovian conditioned stimuli, and these responses depend on input from the basolateral amygdala (BLA). In this study, we examined the mPFC efferent circuits mediating conditioned responding by testing whether specific subsets of mPFC projection neurons receive BLA input and respond to conditioned stimuli. In urethane-anesthetized rats, we identified mPFC neurons that projected to the nucleus accumbens (NAcc) or to the contralateral mPFC (cmPFC) using antidrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 63 publications
1
47
0
Order By: Relevance
“…In addition to the PrL-to-NAcCo projection, maturation of silent synapses in the BLA-to-NAcSh is also essential for incubation of cocaine craving (Lee et al, 2013), suggesting a close connection between the BLA and PrL in modulating NAc-based cocaine-taking behaviors. Indeed, it has been observed that the BLA and mPFC projections gate each other’s influences on NAc-based cellular and behavioral responses (Jackson and Moghaddam, 2001; McGinty and Grace, 2008), likely also involving the NAc core and shell interactions. We speculate that the metastructure of the BLA and PrL projections to the NAc shell and core, as well as the shell-core interaction, are redefined following silent synapse-based remodeling of individual circuits, and the integrated effect mediates the incubation of cocaine craving.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the PrL-to-NAcCo projection, maturation of silent synapses in the BLA-to-NAcSh is also essential for incubation of cocaine craving (Lee et al, 2013), suggesting a close connection between the BLA and PrL in modulating NAc-based cocaine-taking behaviors. Indeed, it has been observed that the BLA and mPFC projections gate each other’s influences on NAc-based cellular and behavioral responses (Jackson and Moghaddam, 2001; McGinty and Grace, 2008), likely also involving the NAc core and shell interactions. We speculate that the metastructure of the BLA and PrL projections to the NAc shell and core, as well as the shell-core interaction, are redefined following silent synapse-based remodeling of individual circuits, and the integrated effect mediates the incubation of cocaine craving.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the cortex in sensitization is not an exception as it is known that the prefrontal cortex and the hippocampus exhibit converging projections to the NAcc and have functional reciprocal connections via indirect pathways (Day et al, 1991;Goto and Grace, 2008). Medial prefrontal neurons, including those projecting to 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 16 the NAcc (McGinty and Grace, 2008), are also excited by conditioned stimuli (Laviolette et al, 2007) and Ball et al (2009) demonstrating that long-lasting locomotor sensitization to MDMA is accompanied by reorganization of synaptic connectivity, not only in NAcc, but also in the medial prefrontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…54,55 The infralimbic cortex has also been implicated in the extinction of previously conditioned behaviors. 56,57,87,88 A recent study in rodents has indicated that projections from the basolateral amygdala, which encodes affective information, and the MdPFC converge within the ventral striatum (nucleus accumbens; McGinty and Grace 58 ), suggesting that the basolateral amygdala may recruit the MdPFC to drive specific sets of nucleus accumbens neurons and thereby influence behavioral responses to conditioned cues. Thus, both infralimbic cortex and MdPFC in rodents appear to be involved in regulation of amygdala-driven behaviors.…”
Section: Voluntary Subprocessesmentioning
confidence: 99%